2015
DOI: 10.1039/c4gc01462f
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-catalyzed regioselective sulfenylation of imidazoheterocycles in PEG400

Abstract: Formation of various 3-arylthioimidazoheterocycles using benign reagents and solvents with harmless by-products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(40 citation statements)
references
References 56 publications
(8 reference statements)
0
40
0
Order By: Relevance
“…

A multicomponent reaction, promoted by molecular iodine and diacetoxyiodobenzene, for the synthesis of (E)-1,3diphenyl-1-butene derivatives from styrene and thiophenol was developed. [26] Furthermore, the iodine-mediated thiolation of substituted anilines [27] and naphthols/naphthylamines, [28] sulfenylation of imidazoheterocycles, [29] and synthesis of 2-arylsulfanylphenols, [30] are examples that demonstrate the importance of iodine in S-C bond formation. Different pathways for the dimerization of styrene.

[a] 3311 Recently, the use of hypervalent [24,25] and molecular iodine in the formation of S-C and S-heteroatom bonds has gained some interest.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…

A multicomponent reaction, promoted by molecular iodine and diacetoxyiodobenzene, for the synthesis of (E)-1,3diphenyl-1-butene derivatives from styrene and thiophenol was developed. [26] Furthermore, the iodine-mediated thiolation of substituted anilines [27] and naphthols/naphthylamines, [28] sulfenylation of imidazoheterocycles, [29] and synthesis of 2-arylsulfanylphenols, [30] are examples that demonstrate the importance of iodine in S-C bond formation. Different pathways for the dimerization of styrene.

[a] 3311 Recently, the use of hypervalent [24,25] and molecular iodine in the formation of S-C and S-heteroatom bonds has gained some interest.

…”
mentioning
confidence: 99%
“…For instance, Wacharasindhu et al exploited the environmental compatibility and readily availability of diacetoxy-iodobenzene (DIB) in the activation of thiols for the construction of S-S and S-N bonds and further applied the method in the sulfenylation of indoles. [26] Furthermore, the iodine-mediated thiolation of substituted anilines [27] and naphthols/naphthylamines, [28] sulfenylation of imidazoheterocycles, [29] and synthesis of 2-arylsulfanylphenols, [30] are examples that demonstrate the importance of iodine in S-C bond formation. In continuation of our interest in the synthesis of organosulfur compounds, [31][32][33][34][35] we herein report a regio-and stereoselective three-component synthesis of novel (E)-1,3-diphenyl-1butene derivatives 7, that contain a sulfur atom, in the absence of a metal or a strong acid catalyst (Scheme 1b).…”
mentioning
confidence: 99%
“…Iodine‐catalyzed sulfenylation of imidazo[1,2‐ a ]pyridines with various thiophenols in the presence of hydrogen peroxide as an oxidizing reagent and in PEG 400 as solvent is described by Hiebel and co‐workers (Scheme ). 3‐Arylthioimidazo heterocycles could be obtained with moderate to high yields . Similar reaction conditions were also applied to synthesize sulfenylated indoles: in the presence of I 2 as catalyst and TBHP as oxidant, for example, various monoarylthioindoles were obtained efficiently.…”
Section: Thiols As Sulfenylation Reagentsmentioning
confidence: 96%
“…3-Arylthioimidazo hetero-cycles could be obtained with moderate to high yields. [4] Similar reaction conditions were also applied to synthesize sulfenylated indoles: in the presence of I 2 as catalyst and TBHP as oxidant, for example, various monoarylthioindoles were obtained efficiently. Moreover, diarylthioindoles could also be generated under these reaction conditions.…”
Section: Thiols As Sulfenylation Reagentsmentioning
confidence: 99%
“…Various research groups have reported the I 2 -catalyzed crossdehydrogenative coupling of arene-/heteroarene-/alkanethiols with differentn ucleophiles in the presence of DMSO,aperoxide, or O 2 as the oxidant( Ta ble1). [83][84][85][86][87][88][89][90][91][92][93][94] The nucleophile attacks 403,w hich is generated by iodination of disulfide 402 resulting from the oxidative dimerization of thiol 401,t op roduce the product 404 with the elimination of HI. Oxidation of HI regenerates I 2 forthe next catalytic cycle.…”
Section: Heteroatom Activation To Form Ah Etàibond As Ak Ey Intermediatementioning
confidence: 99%